(Evapo)Transpiration Measurements Over Vegetated Surfaces as a Key Tool to Assess the Potential Damages of Air Gaseous Pollutant for Plants - Gerosa, Giacomo; Finco, Angelo; Mereu, Simone; Denti, Antonio Ballarin; Marzuoli, Riccardo (IntechOpen, 2011)
None